THE ROLE OF ENDOTHELIN-1 IN VASCULAR HEMOSTASIS OF PERIODONTAL TISSUES - N.V. Yarychkivska (Український стоматологічний альманах)
Generalized data concerning the role of ET-1 as the marker of microcirculation dysfunction in periodontal tissues and its role in the hemostasis in chronic generalized periodontitis are represented in the review. Published information often deals with in vitro investigations and that is why is often controversial and of low practical value. Results of investigations which were analysed in numerous native and foreign scientific publications indicate to the necessity of further study of the role of ET-1 in biochemical processes of the organism and the development and the course of diseases of oral cavity in particular.